2014
DOI: 10.1515/chem-2015-0071
|View full text |Cite
|
Sign up to set email alerts
|

Non-thermal plasma treatment induces MAPK signaling in human monocytes

Abstract: Abstract:The application of non-thermal atmospheric pressure plasma raises a hope for the new wound healing strategies. Next to its antibacterial effect it is known to stimulate skin cells. However, monocytes are also needed for the complex process of a wound healing. This study investigates the impact of plasma on the intracellular signaling events in the primary human monocytes. The proliferative MEK-ERK (MAPK/ERK kinase-extracellular signal-regulated kinase) pathway was activated by short plasma treatment t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…Moreover, the longer the treatment time, the higher was the concentration of both species in the treated media and the reduction of cell viability for both monocytes and MDM. Similar findings have been reported for several cell lines [16,20,38].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, the longer the treatment time, the higher was the concentration of both species in the treated media and the reduction of cell viability for both monocytes and MDM. Similar findings have been reported for several cell lines [16,20,38].…”
Section: Discussionsupporting
confidence: 91%
“…As an example, Kaushik et al [18], reported the cytotoxic effects of CAP on monocytic lymphoma U937 cells and Bekeschus et al [19] demonstrated the differential sensitivity of blood mononuclear cell subpopulations to plasma treatment. Focusing on the effects of plasma on monocytes, the plasma treatment of primary human monocytes can activate the pro-proliferative or pro-apoptotic intracellular signaling cascades, depending on plasma treatment time [20]. Several papers have focused on the plasma treatment of macrophagic populations [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Using transcriptomic profiling, we here wanted to extend on this by understanding the redox signaling responses and molecular pathways in Jurkat and THP‐1 cells following exposure to plasma‐treated medium. Previous experiments showed that several MAP kinases and chaperones were differentially regulated with 30 (Jurkat) and 75 s (THP‐1) treatment time compared to each respective control . Hence, we used these exposure times throughout for in depth transcriptomic analysis.…”
Section: Resultsmentioning
confidence: 99%
“…However, this was done in previous studies. Bundscherer and colleagues have shown that longer plasma treatment times, but not a concentration-matched amount of H 2 O 2, induces ERK-phosphorylation in primary monocytes [93]. Plasma-mediated ERK-phosphorylation was also found in THP-1 cells [94].…”
Section: Discussionmentioning
confidence: 99%